Using heat detection to assist artificial insemination for cattle farmers in Vietnam - Vu Ngoc Dung; Chi Nguyen; Tran Ha; Le Thi Thanh Huyen; Marshall, Karen (International Livestock Research Institute, 2024)
This technical video, produced under the CGIAR Initiative on Sustainable Animal Productivity (2022-2024), provides guidance for farmers, technicians, and agricultural extension workers interested in using heat detection technology for successful cattle insemination. The video highlights key steps for accurately detecting heat in cows, including recognizing behavioral and physiological signs, monitoring cows after insemination, and addressing challenges in heat detection. By mastering this technique, farmers can optimize artificial insemination timing, improving conception rates and cattle productivity.